Directed ortho,ortho'-dimetalation of hydrobenzoin: Rapid access to hydrobenzoin derivatives useful for asymmetric synthesis - Cho, Inhee; Meimetis, Labros; Belding, Lee; Katz, Michael J.; Dudding, Travis; Britton, Robert (Beilstein Journal of Organic Chemistry, 2011)
A variety of ortho,ortho'-disubstituted hydrobenzoin derivatives are readily accessible through a directed ortho,ortho'-dimetalation strategy in which the alcohol functions in hydrobenzoin are deprotonated by n-BuLi and the resulting lithium benzyl alkoxides serve as directed metalation groups. The optimization and scope of this reaction are discussed, and the utility of this process is demonstrated in the one-pot preparation of a number of chiral diols as well as a short synthesis of the chiral ligand Vivol.
Keywords: chiral diol; directed ortho-metalation; hydrobenzoin

(untitled) - Brunel, J. M. (Chem. Rev., 2005)

(untitled) - Seebach, D.; Beck, A. K.; Heckel, A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Rauniyar, V.; Zhai, H.; Hall, D. G. (J. Am. Chem. Soc., 2008)

(untitled) - Mlynarski, J.; Jankowska, J.; Rakiel, B. (Tetrahedron: Asymmetry, 2005)

(untitled) - Mlynarski, J.; Mitura, M. (Tetrahedron Lett., 2004)

(untitled) - Terfort, A.; Brunner, H. (J. Chem. Soc., Perkin Trans. 1, 1996)

(untitled) - Amurrio, D.; Khan, K.; Kündig, E. P. (J. Org. Chem., 1996)

(untitled) - Tomioka, K.; Shindo, M.; Koga, K. (J. Am. Chem. Soc., 1989)

(untitled) - Broeker, J.; Knollmueller, M.; Gaertner, P. (Tetrahedron: Asymmetry, 2006)

(untitled) - Andrus, M. B.; Sekhar, B. B. V. S.; Meredith, E. L.; Dalley, N. K. (Org. Lett., 2000)

(untitled) - Kim, K. S.; Lee, Y. J.; Kim, J. H.; Sung, D. K. (Chem. Commun., 2002)

(untitled) - Mazé, F.; Purpura, M.; Bernaud, F.; Mangeney, P.; Alexakis, A. (Tetrahedron: Asymmetry, 2001)

(untitled) - Marshall, J. A.; Xie, S. (J. Org. Chem., 1995)

(untitled) - Wallace, T. W.; Wardell, I.; Li, K.-D.; Leeming, P.; Redhouse, A. D.; Challand, S. R. (J. Chem. Soc., Perkin Trans. 1, 1995)

(untitled) - Fujioka, H.; Kitagawa, H.; Nagatomi, Y.; Kita, Y. (Tetrahedron: Asymmetry, 1995)

(untitled) - Wyatt, P.; Hudson, A.; Charmant, J.; Orpen, A. G.; Phetmung, H. (Org. Biomol. Chem., 2006)

(untitled) - Wyatt, P.; Warren, S.; McPartlin, M.; Woodroffe, T. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Wang, Z.-M.; Sharpless, K. B. (J. Org. Chem., 1994)

(untitled) - Ikariya, T.; Hashiguchi, S.; Murata, K.; Noyori, R. (Org. Synth., 2005)

(untitled) - Okano, K. (Tetrahedron, 2011)
(For a comprehensive review on the synthesis and applications of hydrobenzoin.)

(untitled) - Kelly, T. R.; Li, Q.; Bhushan, V. (Tetrahedron Lett., 1990)

(untitled) - Cho, I.; Meimetis, L.; Britton, R. (Org. Lett., 2009)

(untitled) - Snieckus, V. (Chem. Rev., 1990)

(untitled) - Granander, J.; Sott, R.; Hilmersson, G. (Tetrahedron: Asymmetry, 2003)

(untitled) - Hirt, U. H.; Spingler, B.; Wirth, T. (J. Org. Chem., 1998)

(untitled) - Panetta, C. A.; Garlick, S. M.; Durst, H. D.; Longo, F. R.; Ward, J. R. (J. Org. Chem., 1990)

(untitled) - Meyer, N.; Seebach, D. (Angew. Chem., Int. Ed. Engl., 1978)

(untitled) - Meyer, N.; Seebach, D. (Chem. Ber., 1980)

(untitled) - Fürstner, A.; Martin, R. (Chem. Lett., 2005)

(untitled) - Negishi, E.-i.; Takahashi, T.; Akiyoshi, K. (J. Organomet. Chem., 1987)

(untitled) - Zhang, H.; Cai, Q.; Ma, D. (J. Org. Chem., 2005)

(untitled) - Masutani, K.; Irie, R.; Katsuki, T. (Chem. Lett., 2002)
(For an unrelated synthesis of this substance.)

(untitled) - Scheiper, B.; Bonnekessel, M.; Krause, H.; Fürstner, A. (J. Org. Chem., 2004)